Getting it right before transplantation: example of a stem cell model with regenerative potential for the CNS - Viero, Cedric; Forostyak, Oksana; Sykova, Eva; Dayanithi, Govindan (Frontiers in Cell and Developmental Biology, 2014)
The burden of neurodegenerative disorders in an aging population has become a challenge for the modern world. While the biomarkers available and the methods of diagnosis have improved to detect the onset of these diseases at early stages, the question of adapted and efficient therapies is still a major issue. The prospect of replacing the loss of functional neural cells remains an attractive but still audacious approach. A huge progress has been made in the generation of neurones derived from human stem cell lines and transplantation assays are tested in animals for a wide range of pathologies of the central nervous system. Here we take one step back and examine neuronal differentiation and the characterisation of neural progenitors derived from human embryonic stem cells. We gather results from our previous studies and present a cell model that was successfully used in functional analyses and engraftment experiments. These neuronal precursors exhibit spontaneous and evoked activity, indicating that their electrophysiological and calcium handling properties are similar to those of matured neurones. Hence this summarised information will serve as a basis to design better stem cell-based therapies to improve neural regeneration.